Analisis SWOT Untuk Pengembangan Strategi Bisnis UMKM Oleh-Oleh Berbasis Tenun Ikat di Toko Jayabaru Maumere - Emilianus Eo Kutu Goo; Noventus Sodi; Theresia Yunita; Chatarina Elvinda; Maria Novita Sari; Barnabas Kevin Keli; Petrus Viktorius Nong Viki Keitimu (Lembaga Pengembangan Kinerja Dosen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economic development, particularly in developing products based on local wisdom. Toko Jayabaru is an MSME that markets Maumere's signature souvenirs made from traditional ikat woven fabric, facing various challenges and opportunities amid business and tourism dynamics. This study aims to identify internal and external factors affecting Toko Jayabaru's performance and formulate appropriate business development strategies through SWOT analysis. The research employs a qualitative descriptive approach with data collection through in-depth interviews with the owner and management of Toko Jayabaru. Data analysis uses the SWOT framework (Strengths, Weaknesses, Opportunities, Threats) to identify the business's strategic position and formulate alternative development strategies. Toko Jayabaru's main strengths lie in strong local cultural identity, authentic product quality, and adequate business experience. Weaknesses include limited digital marketing, restricted production capacity, and lack of derivative product variations. Opportunities encompass Flores tourism sector growth, increasing interest in local products, and potential strategic collaborations. Main threats are competition from similar products, influx of imitation products, and dependence on tourism sector fluctuations. Recommended development strategies include strengthening branding through storytelling, diversifying woven derivative products, optimizing digital marketing, strategic collaboration with tourism stakeholders, enhancing human resource capacity, and implementing customer loyalty programs. Implementation of these strategies is expected to increase MSME competitiveness while preserving Maumere's local culture.